Selected misdemeanors against monuments - Klimczyk, Agata (Journal of Education, Health and Sport, 2016)
The aim of the work is to present selected aspects misdemeanors against monuments and the possibility of counteracting them.The author has used: the method of legal analysis and literature study. It was moved, among others issues in which cases occur misconduct, when and what measures can be taken to prevent it. The aim of this paper is to present the matter directly. Attention also was paid to the role The Provincial Monuments Conservator and the Minister of Culture and National Heritage.